2019
DOI: 10.25000/acem.563986
|View full text |Cite
|
Sign up to set email alerts
|

Hipertansif hastalarda plazma aterojenik indeks düzeylerinin incelenmesi

Abstract: Aim: Hypertension is a major risk factor for cardiovascular system. Recent studies showed that atherogenic index of plasma (AIP) has a strong association with cardiovascular morbidity, all-cause mortality, atherosclerosis and severity of coronary artery disease. It also has a relationship with endothelial damage in hypertensive patients. With this study we aim to investigate the association between AIP and hypertension. Methods: A total of 213 patients were enrolled for the study. Patients with previous hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…High triglyceride and low HDL-C levels are both risk factors for cardiovascular diseases. 35 The AIP combines these two risk factors and several studies performed on this subject and showed that the AIP is associated with atherosclerosis, cardiovascular diseases, diabetes mellitus, hypertension, vascular and endothelial damage 16 , 17 , 18 , 19 , 20 . SARS-CoV-2 affects cardiovascular system on different levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High triglyceride and low HDL-C levels are both risk factors for cardiovascular diseases. 35 The AIP combines these two risk factors and several studies performed on this subject and showed that the AIP is associated with atherosclerosis, cardiovascular diseases, diabetes mellitus, hypertension, vascular and endothelial damage 16 , 17 , 18 , 19 , 20 . SARS-CoV-2 affects cardiovascular system on different levels.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The AIP is associated with chronic diseases such as diabetes, hypertension and cardiovascular disease. 16 , 17 , 18 , 19 , 20 Additionally, the relationship between the severity of viral infections and the AIP has been identified. 21 Moreover, there are studies which discuss the impact of SARS-CoV on the disorders of patients’ lipid profile in long-term, while their short term effects are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…AIP is already a defined risk factor for cardiovascular system diseases. 3 , 4 , 5 Our aim in this study was to show that AIP is an indicator of COVID-19 mortality independent of cardiovascular diseases. Also as you mentioned ethnicity is important for COVID-19 patients it would be better if we specify the ethnic differences of our patients.…”
mentioning
confidence: 99%
“…We actually mentioned the relationship between AIP and several illnesses like cardiovascular diseases, atherosclerosis, diabetes mellitus, hypertension. 3 , 4 , 5 , 6 , 7 …”
mentioning
confidence: 99%